If it's not what You are looking for type in the equation solver your own equation and let us solve it.
4x=3(49-x)
We simplify the equation to the form, which is simple to understand
4x=3(49-x)
Reorder the terms in parentheses
4x=+(+147-3x)
Remove unnecessary parentheses
+4x=+147-3x
We move all terms containing x to the left and all other terms to the right.
+4x+3x=+147
We simplify left and right side of the equation.
+7x=+147
We divide both sides of the equation by 7 to get x.
x=21
| 5+h=-6 | | .67x=5 | | 17.50+4p=53.50 | | 7-5m=45 | | 2(5x+2)=8x | | -4(3x+1)+x=3x+10 | | .5*.5*.5*.5= | | 10-4x=28 | | 98x=-1 | | x^2-19x+9=0 | | 14x-2=7x-51 | | 3(6x)=200 | | 5(m-3)+2m=28 | | (x-1)7=8x | | C+9=-13 | | 9r+5=71 | | 10+10+(-7)+(-5)= | | 15r+6=54 | | -47+47=-24p-14p | | 3x=2x+16 | | -47+58=-24p-14p | | 6x-15=3x+1 | | -15=0.5x-0.8x | | -8y=-64 | | -168=-16x-8x | | 8-y=-64 | | 9x-5x=42 | | -r-15r=128 | | x^2+8x=14 | | 2x^3-8=0 | | u^2+9u+20=0 | | 6-5(6)= |